Different counselors, many options: Career guidance and career plans in secondary schools - Bernd Fitzenberger; Annette Hillerich-Sigg; Maresa Sprietsma (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2019)
Career guidance assists students with the school-to-work transition. Based on a survey in secondary schools in Germany, we analyze career guidance activities and how these affect career plans. The take-up of career guidance depends upon the school track attended and upon the school and class room context, while personal characteristics are hardly relevant. The effects of counseling depend upon the counselor. Counseling by the employment agency reduces plans for educational upgrading and increases the probability of applying for an apprenticeship, while the effects of school counselors work in the opposite direction for lower track students.
Keywords: J24; I28; I21; 330; educational aspirations; career guidance; counseling; career planning; school-to-work transition; secondary school